African union summit in Accra : time for African leaders to make human rights count and implement their promises and commitments - Amnesty International (2007)
Ahead of the Ordinary Session of the African Union (AU), to be held in Accra, Ghana between 25 June and 3 July 2007, Amnesty International is urging African leaders to seize the opportunity of the meeting to put human rights first, and to implement their promises and commitments. The document includes recommendation which highlight some areas which African governments and the AU should consider if they are to effectively address the enormous human rights challenges confronting the continent.